2018
DOI: 10.1177/0963689718796196
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Transplantation of Human Amniotic Epithelial Cells in the Treatment of Autoimmune Uveitis in Rats

Abstract: As a featured ocular inflammatory disease, autoimmune uveitis is the major cause of blindness in the clinic. Although current immunosuppressive regimens can alleviate the progression of autoimmune uveitis, they have serious side effects. Therefore, an alternative therapeutic strategy is urgently required. The present study investigated the therapeutic efficacy of human amniotic epithelial cells (hAECs) on autoimmune uveitis in a rat model. Herein, experimental autoimmune uveitis (EAU) was induced in rats via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…It is rather complicated to illustrate the deep mechanisms by which hAESCs suppress an excessive immune response. It was reported that hAESCs are capable of preventing macrophage and T cell infiltration into the lesion area and maintaining the proper portions of different T cell subtypes by modulating the cytokine concentration inside the microenvironment in certain autoimmune disorder models [ 134 , 135 ]. Actually, previous research has focused on the anti-inflammation effects of conditioned medium and cytokines from hAESCs.…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
See 3 more Smart Citations
“…It is rather complicated to illustrate the deep mechanisms by which hAESCs suppress an excessive immune response. It was reported that hAESCs are capable of preventing macrophage and T cell infiltration into the lesion area and maintaining the proper portions of different T cell subtypes by modulating the cytokine concentration inside the microenvironment in certain autoimmune disorder models [ 134 , 135 ]. Actually, previous research has focused on the anti-inflammation effects of conditioned medium and cytokines from hAESCs.…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
“…The latter is considered to be a pivotal subtype in inhibiting inflammation and encouraging tissue repair. Three types of cytokines related to anti-inflammation have been proven to be produced by hAESCs and amniotic tissue: (1) apoptosis inducers such as tumor necrosis factor-α (TNF-α), Fas ligand (FasL), and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL); (2) macrophage migration inhibitors such as transforming growth factor-β (TGF-β) and macrophage migration-inhibitory factor (MIF); and (3) other antiangiogenic and anti-inflammatory proteins including interleukin-1 receptor antagonist (IL-1ra), interleukin-10 (IL-10), tissue inhibitors of metalloproteinase (TIMPs), collagen XVⅢ, and thrombopondin-1 [ 134 , 135 , 136 , 137 , 138 ]. Data indicate that these cytokines are critical in the hAESC- and amniotic-tissue-mediated anti-inflammation process.…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
See 2 more Smart Citations
“…Unlike human ESCs, hAECs do not express telomerase and thus are not tumorigenic upon transplantation (Miki, 2018). Based on these excellent properties, hAECs have been widely applied in the pre-clinical treatment of many diseases, e.g., liver cirrhosis (Lin et al, 2015), pulmonary damages (Zhu et al, 2017), neurological disorders (Sankar & Muthusamy, 2003), autoimmune uveitis (Li et al, 2018), diabetes (Luo et al, 2019), early Achilles tendon defects (Barboni et al, 2018), as well as aging-related diseases (Di Germanio et al, 2016). Therefore, hAECs possess considerable therapeutic potentials in regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%